Identifikasi Siswa SD yang Bekerja Sebagai Anak Jalanan di Kota Surabaya - Singgih Susilo (Sekolah Dasar : Kajian Teori dan Praktik Pendidikan, 2007)
Abstract: Economic stress as a consequence of multi-dimensional crisis make some members of our society become economically marginal. Some of elementary students become labor for improving their family economic condition. The purpose of this research was to identify street children who become elementary school students. The results found the intentions of the students became street children are to get some money for school tuition and to improve economic family. The management of student’s regular street activities time was based on vacancy of school time.